Análise Econométrica das Exportações de Produtos Siderúrgicos - Araújo, Leonardo Sales (2006)
The objective of this dissertation is to analyze the response of the exported quantities of steel products to variables which represent price, domestic income and foreign income, through an empirical analysis of chosen steel products: semi-finished steels, flat steels (representing all types of flat products produced in Brazil), uncoated steels, coated steels, special-alloy steels, long steels (representing all types of long products produced in Brazil), steel bars, wire-rod, steel shapes and concrete reinforcing bars. The price variables are represented by the product s real price (having already been removed the effects of exchange rates and the costs of the steel sector). The domestic income variable is represented by the Brazilian Gross Domestic Product and as far as the foreign income, as a proxy variable, the Gross Domestic Product of the United States is used. The analysis concentrates only on the long run behavior. First, unit root tests were used. Then, the cointegration technique was used to analyze the long term relationship among the variables. This long term relationship measures the elasticity of the exported quantities of steel products to variations in price, domestic income and foreign income